An activity-based probe for antimicrobial target DXP synthase, a thiamin diphosphate-dependent enzyme - Coco, Lauren B.; Freel Meyers, Caren L. (Frontiers in Chemical Biology, 2024)
This work reports an alkyl acetylphosphonate (alkylAP) activity-based probe (ABP) for 1deoxy-D-xylulose 5-phosphate synthase DXPS, a promising antimicrobial target. This essential thiamin diphosphate (ThDP)-dependent enzyme operates at a branchpoint in bacterial central metabolism and is believed to play key roles in pathogen adaptation during infection. How different bacterial pathogens harness DXPS activity to adapt and survive within host environments remains incompletely understood, and tools for probing DXPS function in different contexts of infection are lacking. Here, we have developed alkylAP-based ABP 1, designed to react with the ThDP cofactor on active DXPS to form a stable C2a-phosphonolactylThDP adduct which subsequently crosslinks to the DXPS active site upon photoactivation. ABP 1 displays low micromolar potency against DXPS and dose-dependent labeling of DXPS that is blocked by alkylAP-based inhibitors. The probe displays selectivity for DXPS over ThDP-dependent enzymes and is capable of detecting active DXPS in a complex proteome. These studies represent an important advance toward development of tools to probe DXPS function in different contexts of bacterial infection, and for drug discovery efforts on this target. Word count: 5,448 Figure count: 9 figures in Manuscript; 12 figures in Supplementary MaterialTable count: 1 table in Supplementary Material 1 Introduction Identification of novel antimicrobial targets is essential to address the continued global threat of antimicrobial resistance (World Health Organization 2022). Bacterial central metabolism remains relatively underexplored, yet promising, for development of new antimicrobial strategies (Murima, McKinney, and Pethe 2014; Tong and Brown 2023). Targeting pathogen adaptation is a particularly intriguing facet of developing this target space. Bacteria undergo metabolic remodeling in response to fluctuations in nutrient availability within the host (Passalacqua,